Preferences for vaccines against children's diarrheal illness among mothers in Poland and Hungary. Issue 40 (25th September 2018) - Poulos, Christine; Standaert, Baudouin; Sloesen, Brigitte; Stryjewska, Izabella; Janitsary, Anna; Hauber, Brett
Highlights: We evaluated mothers' preferences for rotavirus vaccination in Hungary and Poland. Vaccine cost and effectiveness and disease severity are key drivers for vaccination. In Poland, disruptions in work, child care, and routines also motivate mothers. In Hungary, working mothers are less likely than non-working mothers to opt out. Abstract: Purpose: Although the World Health Organization recommends universal rotavirus immunization, uptake of the vaccine is low in Poland and Hungary, where it is not covered by the National Immunization Program. This study aimed to quantify mothers' preferences for vaccines preventing children's diarrheal illness and to examine whether willingness to vaccinate varies with working status. Methods: Mothers of children aged <3 years living in Poland and Hungary completed an online discrete-choice experiment survey. In each of 9 choice questions, respondents indicated whether they preferred no vaccination or one of two hypothetical vaccine profiles described in terms of 6 features. Vaccine preference parameters were estimated for working and non-working mothers using a random-parameter logit model and were used to calculate the relative importance of changes in vaccine features. Results: 350 mothers in Poland and 350 mothers in Hungary were surveyed. Of the attributes evaluated, changes in vaccine cost were most important in both countries, followed by changes in severity of illness prevented, vaccine effectiveness, mode of administration, duration of illness prevented, and number of doses. Mothers in both countries had a strong preference for vaccination versus no vaccination, which was more pronounced among working mothers. In Poland, working mothers placed less weight on effectiveness, illness severity, and cost than non-working mothers and were more likely to rate disruptions in work, child care, and routines as important reasons to vaccinate. In Hungary, working mothers were statistically significantly less likely to opt out of vaccination than non-working mothers. Preference for vaccination itself, relative to improving vaccine effectiveness (from 50% to 90% effective), was 7 times greater among working than among non-working mothers in Poland but was not considerably different between working and non-working mothers in Hungary. Conclusions: Polish and Hungarian working mothers are more likely to vaccinate children against diarrheal illness than non-working mothers.